BEYOND THE CHECKLIST: FISHERIES INSIGHTS FROM TAXONOMIC DISCOVERY AND ETP PROTECTION - B Mabel Manjaji-Matsumoto (16932984) (2025)
This conference contribution was presented by B Mabel Manjaji-Matsumoto. Borneo Marine Research Institute, Universiti Malaysia Sabah, Malaysia, (18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. 2025). Advancing the conservation of marine Endangered, Threatened, and Protected (ETP) species necessitates rigorous taxonomic research and innovative survey methodologies. This study presents an integrative approach utilizing comprehensive field assessments, structured fisher interviews, and market surveys to document species diversity across Malaysian coastal ecosystems. The survey covered 65 species (20 families) of sharks, and 81 species (16 families) of rays, alongside 7 previously undocumented discoveries. The taxonomic findings provided critical inputs for Malaysia's Ecosystem Approach to Fisheries Management (EAFM) for sharks and rays, where species status assessments directly influenced management recommendations. Additionally, taxonomic research contributed expert views to Malaysia's National Plan of Action (NPOA) for sharks, translating taxonomic discoveries into actionable conservation strategies and catch regulation frameworks. Collaborative engagement with local communities and regulatory bodies facilitated standardized methodologies and ensured compliance with national biodiversity monitoring requirements. The research demonstrates how taxonomic expertise extends beyond species documentation to shape practical fisheries policy, including habitat protection measures, trade restrictions, and sustainable harvest guidelines. This work exemplifies the transition from taxonomic discovery to fisheries governance, highlighting how rigorous species identification and collaborative partnerships drive evidence-based marine conservation policy and sustainable fisheries management in Southeast Asian waters. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx